PERSEPSI SISWA TERHADAP DISIPLIN GURU DALAM PENINGKATKAN MOTIVASI BELAJAR - Arif Samsurrijal (Al Hikmah: Jurnal Studi Keislaman, 2013)
Teachers as educators in the school should have a discipline that must be executed with great sincerity; teachers should set an example for their students, in order to form a good perception of discipline teachers on students. Discipline on how to run the teacher influenced the perception of students watched because perception is the basis for a person to act or behave.Teacher as educators as well as managing the learning process should be able to behave or act properly. It can of course influence on students' motivation tendency towards a positive, understanding and applying rules and norms both within the school and outside. This is achieved by realizing the importance of teacher discipline and strives to improve it.With high teacher discipline will give a good perception for students, from what he saw so as to improve learning motivation in the course. For teachers with a high discipline can be a driving force in increasing students' motivation towards the positive and the awareness of the importance of the student as a student assignment.